Effects of blended learning through lab-rotation and flipped classroom model on academic performance and self-regulated learning among form four chemistry students - Abdul Aziz, Mohd Ariffuddin (2022)
Blended learning is known as combination between the online learning and face-to-face learning. In this study, there were two blended learning models had been tested namely as lab-rotation and flipped classroom. Blended learning through lab-rotation (BLLR) model required the students to learn by rotation between the computer laboratory for online learning session and classroom for face-to-face learning. For the blended learning through flipped classroom (BLFC) model, the students are required to learn earlier at home using the online learning platform then, discuss the teaching task during the faceto- face learning session at the school. The failure of Malaysian students to achieve a minimum average score in PISA and TIMSS for four consecutive years causes them to have difficulty in learning chemistry, especially for electrochemistry topics, when they are in form four level (students at the age of 16). Students have several misconceptions about electrochemistry, which they must understand at the three different levels of modes as stated by Johnstone's Chemistry Triangle (1993) model. The researcher implements the BLLR model and BLFC model to overcome the problems. The study aimed to investigate the effects of blended learning through lab-rotation model and flipped classroom model on the academic performance and self-regulated learning (SRL) among the form four chemistry students. The research design used in this study is mix-method explanatory design with a quantitative (ANOVA and ANCOVA) followed by qualitative (semi-structured interview) to give comprehensive understanding of the findings. For the quantitative part, quasi-experimental featuring a non-randomized control group with pre-test and post-test which included a retention test was used in this study. At the end of the treatment, the researcher had conducted a semistructured interviews for collecting qualitative data. The total respondents involved in this study were 92 Form Four chemistry students. The respondents were random assigned into three groups, namely as the BLLR model group (Experimental 1), BLFC group (Experimental 2) and F2F traditional learning method group (Control). The online learning platform chosen in this study is Google Classroom. The instruments used in this study were academic performance test, which based on Electrochemistry’s topic in ‘Sijil Pelajaran Malaysia’ (SPM), SRL questionnaires and a semi-structured interview questions to explore students’ perceptions on BLLR model, BLFC model and F2F traditional learning method. The findings of the study revealed that BLLR model, BLFC model and F2F traditional learning method had improved students’ academic performance and SRL among the respondents. There was significant difference at the post-test level for academic performance among the three groups (F (2, 88) = 118.979 and a significant level of .000 (p < .05), BLLR model showed the highest scores followed by BLFC model and F2F traditional learning method. For the SRL, there was significant difference at the post-test level among the three groups (F (2, 88) = 48.648 and a significant level of .000 (p < .05), BLFC model showed the highest scores followed by BLLR model and F2F traditional learning. At the retention test level, for academic performance test there was significant different among the three groups (F (2, 88) = 294.797 and a significant level of .000 (p < .05), BLFC model showed the highest scores followed by BLLR model and F2F traditional learning. For SRL at the retention test level, there was significant different among the three groups (F (2, 88) = 29.083 and a significant level of .000 (p < .05), BLFC model showed the highest scores followed by BLLR model and F2F traditional learning method. The findings in qualitative part through the semi-structured interviews showed that the respondents in the BLLR model and BLFC model agreed that these methods were effective, interesting and convenient to improve their academic performance and SRL. The findings revealed that the BLLR model had a potential to improve academic performance at the post-test level while the BLFC model at the retention level. BLFC model showed the effective method of instruction in enhancing SRL and retained it as well. These findings suggest that BLFC model is the most effective instruction to improve academic performance and SRL compared to BLLR and F2F traditional learning method. This instructional method provides an alternative way in teaching and learning by implementing constructivism theory through the Google Classroom online learning platform to enhance the academic performance and SRL among the secondary school students. Moreover, during the global pandemic COVID-19, policymakers and school principals should implement the BLLR and BLFC models to support students in teaching and learning, as well as in continuing the Science Technology Engineering and Mathematics (STEM) program at the tertiary level.